Highly tumor-specific DNA nanostructures discovered by in vivo screening of a nucleic acid cage library and their applications in tumor-targeted drug delivery. (March 2019) - Kim, Kyoung-Ran; Kang, Seong Jae; Lee, A-Young; Hwang, Dohyeon; Park, Miri; Park, Haedong; Kim, Sanghee; Hur, Kahyun; Chung, Hak Suk; Mao, Chengde; Ahn, Dae-Ro
Abstract: Enormous efforts have been made to harness nanoparticles showing extravasation around tumors for tumor-targeted drug carriers. Owing to the complexity of in vivo environments, however, it is very difficult to rationally design a nanoconstruct showing high tumor specificity. Here, we show an approach to develop tumor-specific drug carriers by screening a library of self-assembled nucleic acid cages in vivo. After preparation of a library of 16 nucleic acid cages by combining the sugar backbone and the shape of cages, we screened the biodistribution of the cages intravenously injected into tumor-bearing mice, to discover the cages with high tumor-specificity. This tumor specificity was found to be closely related with serum stability, cancer cell uptake efficiency, and macrophage evasion rate. We further utilized the cages showing high tumor specificity as carriers for the delivery of not only a cytotoxic small molecule drug but also a macromolecular apoptotic protein exclusively into the tumor tissue to induce tumor-specific damage. The results demonstrate that our library-based strategy to discover tumor-targeted carriers can be an efficient way to develop anti-cancer nanomedicines with tumor specificity and enhanced potency. Graphical abstract: Highlights: A library of 16 nucleic acid cages has been prepared and screened for high tumor specificity in vivo. The tumor-specificity was found to be closely related with serum stabilitycellular uptake efficiency of cages. Highly tumor-specific cages have been employed as carriers for the tumor-targeted delivery of apoptotic molecules.